Relations of Platelet Ca2+ Handling and Membrane Microviscosity to Vascular Tone and Restenosis after Angioplasty in Human Coronary Artery - Feuvre, Claude Le; Sang, Kim-Hanh Le Quan; Brunet, Annie; Catuli, Didier; Metzger, Jean-Philippe; Vacheron, André; Devynck, Marie-Aude (Thrombosis and Haemostasis, 1998)
This study was designed to assess whether platelet Ca2+ handling or membrane microviscosity could be considered as indexes of vascular tone, or could help to predict an increased risk of restenosis after coronary angioplasty. Vascular tone was quantified in 21 patients with stable angina by the vasodilator response to sin-1 intracoronary injection in the reference coronary segment and by the importance of the acute recoil after angioplasty in the narrowed segment. The degree of restenosis was quantified by coronary angiography 6 months later.Individual values of relative sin-1-induced changes in the reference coronary diameter were positively correlated with cytosolic Ca2+ concentration in unstimulated platelets, irrespective of the extracellular Ca2+ concentration (p <0.01). This relationship was also observed with the thrombin-evoked Ca2+ changes, measured in the absence of a Ca2+ influx (p = 0.01). No relationship was found between sin-1-induced coronary changes and membrane microviscosity evaluated by TMADPH and DPH anisotropies or platelet volume, or between degree of acute recoil and platelet characteristics.In conclusion, platelet Ca2+ reflects the vasodilating efficacy in response to sin-1, but cannot help to predict restenosis after coronary angioplasty.